KIAI DAN POLITIK: MENGINTIP MOTIF KIAI NU (NAHDLATUL ULAMA) DALAM PEMILU 2009 DI GLENMORE KABUPATEN BANYUWANGI - H. Sadi H. Sadi (Khazanah Pendidikan, 2016)
Kiai involvement in Indonesian politics is an integral part in the history of Indonesian politics. Affirmation political role Kiai increasingly finding space and form institutionalized when Jam'iyah Nahdlatul Ulama was founded in 1926. The accumulation of social and economic status, coupled with the extent of religious knowledge, making Kiai as a charismatic leader who respected in society so that a Kiai become a reference source in every issue that society confronted. The authorized capital of which are owned Kiai is the theological legitimacy, where the figure Kiai regarded as the heir to the Prophet (Al Ulama 'Warasatul An Biya'). It is not surprising then that is a very strategic position it became the basis of confirmation of the legitimacy and role in society Kiai. In this study seeks to explain the diversity of political attitudes Kiai and also to answer the motive behind Kiai involved in Election Year 2009 in Glenmore District Banyuwangi, to determine the political role Kiai in the General Election of 2009. Keywords: kiai, politics, elections